THE PERMIAN ANTITROPICAL FUSULINOIDEAN GENUS MONODIEXODINA: DISTRIBUTION, TAXONOMY, PALEOBIOGEOGRAPHY AND PALEOECOLOGY - Ueno K. (My University, 2006)
All the documented occurrences with illustration of specimens of the Permian fusulinoidean genus Monodiexodina from a total of 33 areas in 11 regions are reviewed and their taxonomic positions are reexamined in this paper. Among 17 species (including two subspecies) of Monodiexodina in the current taxonomy, the following 10 species are recognized as valid: M. kattaensis, M. wanneri, M. caracorumensis, M. sutchanica, M. shiptoni, M. kumensis, M. wanganensis, M. neimongolensis, M. delicata, and M. rhaphidoformis. In addition, species once referred to Monodiexodina but now should be excluded from the genus are also investigated in terms of their generic positions. In reconstructed mid-Permian paleomap, Monodiexodina-bearing areas can be restored to either northern or southern middle latitudes between high latitudinal cool/cold-water climatic realm and paleo-tropical warm-water realm. These two middle latitudinal areas, each corresponding to the Northern and Southern Transitional Zones, respectively, can be best interpreted climatologically as mesothermal, warm temperate belts in both hemispheres, thus suggesting the genus to be a paleobiogeographically typical antitropical fusulinoidean taxon. Moreover, the genus is generally found in a monotypic, crowded manner in sandy sediments with their shells being often aligned uni-directionally. This mode of occurrence of Monodiexodina strongly suggests that it was adapted to shallow-marine, high-energy environments, which would probably be essentially maintained by the acquisition of highly elongated fusiform/subcylindrical shells with well-developed polar torsion. This morphological feature is adapted to increase septal pores per unit area in polar regions, thus increasing possibility to develop more pseudopodia on both sides of test. It probably has a functional significance for not only locomotion but also anchoring their tests on the surface of bottom sediments in agitated water conditions. The genus itself is considered to be a rather long-ranging taxon from the late Yakhtashian (=Artinskian) to the early Midian (=Capitanian). It is, therefore, concluded that Monodiexodina had an opportunistic character, occurring repeatedly only when favorable, high-energy conditions, such as sand shoal, appeared in warm temperate climatic belts in both hemispheres. Monodiexodina originated in the Southern Transitional Zone from an elongated Eoparafusulina stock at late Early Permian (around late Artinskian) time. It flourished in southern middle latitudinal areas in latest Early and early Middle Permian time. The genus then migrated to the northern hemisphere (Northern Transitional Zone) by some dispersion mechanism at around the early Middle Permian, and prevailed there during the remaining period of the Middle Permian. © 2005 Elsevier Ltd. All rights reserved.
Keywords: ANTITROPICAL; MONODIEXODINA; PALEOBIOGEOGRAPHY; PALEOECOLOGY; PERMIAN; TAXONOMY; Paleozoic::Permian; Палеозой::Пермская